Numerical Analysis of Magnetic Plasmonic Resonance Modes in Three-Dimension Split Ring Resonator Metamaterials - Wei Wang; Feng-Ping Yan; Si-Yu Tan; Hai-Su Li; Xue-Mei Du; Hong Zhou; Ya-Fei Hou (IEEE Photonics Journal)
Magnetic resonators based on metamaterials are valuable for numerous applications including perfect absorber, sensing and medical imaging. However, due to the existence of the difficulty in magnetic excitation in planar metasurface, the study of magnetic metamaterial resonators is less reported, particularly in contrast to the electrical resonators. In this paper, the three-dimensional split ring resonator (SRR) metamaterials featuring dual-band magnetic plasmonic resonance modes are proposed and numerically analyzed. We calculate the electromagnetic field distributions of the three-dimensional metamaterials at the resonant frequencies to elucidate the resonant characteristics of the dual modes (fundamental LC mode and high-order magnetic plasmonic resonance mode). The influences of geometric parameters of the constituent meta-atoms on the resonance frequencies of the two resonance modes are analyzed by numerical calculations. The results show that the resonance frequency of the high-order magnetic resonance mode is nearly independent of the standing columns of the metamaterials owing to the special resonant characteristic of the high-order mode. Benefiting from the independence, the frequency interval between the dual modes can be customized by adjusting the dimensions of the column. In addition, by tuning the dimension of the columns, the quality factors of the resonances can reach the highest value of 176 for LC mode and 270 for the high-order mode, respectively. In light of practical application, we evaluate refractive index sensing performance of the proposed metamaterials, the maximum sensitivity can reach 474 GHz/RIU for LC mode and 446 GHz/RIU for high-order resonance, respectively. We also explore the universality of the special resonant characteristic of the high-order mode in other similar three-dimension SRR metamaterials, which shows all of these three-dimension magnetic plasmonic metamaterials provide potential platforms for multiband magnetic metamaterial applications.